Curitiba practice in implementing BRT as a sustainable urban transportation system &its Application in the City of Baghdad - Mahmoud Mohammed, Aws (International Journal of Psychosocial Rehabilitation, 2020)
The human need for transportation has existed from the dawn of time, and its subject was connected to man's constant movement as he traveled from one location to another in search of life's necessities. Over the years, economic and industrial development faced by the world's cities in general, including Arab countries, has led to the presence of many urban problems, including public transport issues, often reflected in their visual and audible forms in busy and noisy roads, traffic blockage, waste, and environmental pollution. Through this, the need arose for the existence of many systems and means for social, economic, and political life issues within these cities, including transportation and transportation systems, which are considered to be a vital cause to insure stable urban cities throughout the numerous cities around the globe, who consider the transportation segment to be playing an important role for every developed and developing country at the cultural, economic, social, and urban levels. Sustainable transportation systems are a keystone for the economical success and wealth of countries. in addition to their important role in fighting climate change in the world by dropping the level of air pollution, especially in the crowded metropolitan cities that are extended in growth at a high pace, in particular in the developing countries. Curitiba in Brazil is considered to be the first city in the world to implement a successful (BRT) bus rapid transit system; then many cities in different countries around the world imitated this system since it proved to be a very successful mode of public transport. In this research the main goal is to find the accessibility of implementing this model of public transport in the cities of Iraq in general and the capital of Baghdad in particular .